2014
DOI: 10.1002/cbic.201402548
|View full text |Cite
|
Sign up to set email alerts
|

Far‐Red Fluorogenic Probes for Esterase and Lipase Detection

Abstract: Fluorogenic enzyme probes go from a dark to a bright state following hydrolysis and can provide a sensitive, real-time readout of enzyme activity. They are useful for examining enzymatic activity in bacteria, including the human pathogen Mycobacterium tuberculosis. Herein, we describe two fluorogenic esterase probes derived from the far-red fluorophore 7-hydroxy-9H-(1,3-dichloro-9,9-dimethylacridin-2-one) (DDAO). These probes offer enhanced optical properties compared to existing esterase probes because the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 45 publications
1
45
0
Order By: Relevance
“…The design and use of fluorogenic compounds with fluorescent scaffolds emitting red or blue to violet fluorescence [3,8] opens up the combined use of GFP expression after genetic modification of bacteria [25]. This would give the possibility to determine protein interaction in vivo by multiplexing fluorescence measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and use of fluorogenic compounds with fluorescent scaffolds emitting red or blue to violet fluorescence [3,8] opens up the combined use of GFP expression after genetic modification of bacteria [25]. This would give the possibility to determine protein interaction in vivo by multiplexing fluorescence measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Novel applications with those chemical compounds for bacterial detection [4][5][6], metabolic characterization [2,7,8], drug development [9], preclinical studies [10], and screening for antibiotic resistance [11] are reported.…”
Section: Introductionmentioning
confidence: 99%
“…8 Conjugation of fluorogenic esterase-activated probes to biomolecules can provide detailed spatiotemporal information about biomolecular uptake and localization in live cells. 3a,9 These biomolecule–probe conjugates are, however, typically internalized by endocytic vesicles and can be exposed therein to acidity as low as pH 4.5, 10 making insensitivity to low pH essential to probe function.…”
Section: Introductionmentioning
confidence: 99%
“…With fluorinated Oregon green, destabilization of the masked substrate was thought to stem from inductive effects resulting in lowered p K a of the conjugate acid of the fluorescein leaving group. 8d Accordingly, design strategies for stable fluorogenic esterase probes have relied heavily on interjecting self-immolative linkers with a higher p K a between the low p K a fluorophore and the site of enzymatic cleavage (Scheme 1). 12 Platforms for such auto-immolative linkers include the acetoxymethyl (AM) ether, 8d,12 quinone methides, 14 and the trimethyl lock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation